Sosialisasi Adaptasi Kebiasaan Baru Pada Ekowisata Mangrove Telok Berdiri, Desa Sungai Kupah, Kecamatan Sungai Kakap, Kabupaten Kubu Raya - Leony Agustine M; Fitra Wira Hadinata; Yunita Magrima Anzani (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Sungai Kupah Village has a Tourism Awareness Group (POKDARWIS) consisting of 30 people. Most of the group members work as fishermen or coconut gardeners. The tourist location managed by the group is in the form of mangrove tourism. This tour is equipped with mangrove tracking facilities, photo spots, canteens, toilets, parking lots. Every month no less than 2,000 visitors before the COVID-19 pandemic. During the pandemic, the number of visitors decreased by almost 70%. Reducing the number of visitors has an impact on decreasing people's income. Therefore, the Mangrove Tourism Awareness Group in Sungai Kupah, which is a partner, hopes to collaborate with universities so that they can provide training assistance or input knowledge about efforts to improve management systems for the development of mangrove tourism in the midst of the COVID-19 pandemic. Lecturers play a role in implementing the Tri Dharma of Higher Education, namely Community Service in the form of participating in empowering and interacting with the community. The goal in partner PKM is POKDARWIS Ecotourism Stand Telok related to the implementation of the CHSE protocol in the management of tourism activities